A Case of Carcinoid Likely Causing Jejunal Intussusception. (16th March 2014) - Matulich, Jennifer; Thurston, Kelly; Galvan, Dan; Misra, Subhasis
Abstract : A 34-year-old female was admitted to Emergency Department with an abrupt onset of diffuse abdominal pain. A CT scan done prior to her transfer revealed significant dilated loops of bowel as well as multiple target signs with likely torsed bowel. The patient consented to an exploratory laparotomy. During surgery, the proximal jejunum was found to be intussuscepted, a rare finding in an adult. There was evidence of mesenteric foreshortening throughout the small bowel and multiple whitish lesions within the mesentery, both consistent with the desmoplastic response that is characteristic of carcinoid. The interest for this case report comes from the patient's surgical findings of jejunal intussusception as well as her extensive history, which includes a bowel resection with an ileocolic anastomosis for presumed ischemia and a carcinoid tumor in the stomach which had been removed endoscopically.